Biofidelic neck influences head kinematics of parietal and occipital impacts following short falls in infants. (September 2015) - Sullivan, Sarah; Coats, Brittany; Margulies, Susan S.
Highlights: Falls are a major cause of traumatic head injury in children. Biomechanics can inform the evaluation of injury risk and design of mitigating strategies. We used a state-of-the-art custom surrogate with life-like neck, skull, and brain properties to study parietal and occipital impacts after head-first falls onto 4 impact surfaces from 3 fall heights. The improved biofidelity of the neck lowered impact forces, angular accelerations, and velocities, and produced predominantly sagittal rotations after occipital impact. Impact site influenced head response, and injury risk due to short falls should take into account the fall height, impact surface and head impact location. Abstract: Falls are a major cause of traumatic head injury in children. Understanding head kinematics during low height falls is essential for evaluating injury risk and designing mitigating strategies. Typically, these measurements are made with commercial anthropomorphic infant surrogates, but these surrogates are designed based on adult biomechanical data. In this study, we improve upon the state-of-the-art anthropomorphic testing devices by incorporating new infant cadaver neck bending and tensile data. We then measure head kinematics following head-first falls onto 4 impact surfaces from 3 fall heights with occipital and parietal head impact locations. The biofidelic skull compliance and neck properties of the improved infant surrogate significantly influenced the measured kinematic loads, decreasing the measured impact force and peak angular accelerations, lowering the expected injury risk. Occipital and parietal impacts exhibited distinct kinematic responses in primary head rotation direction and the magnitude of the rotational velocities and accelerations, with larger angular velocities as the head rebounded after occipital impacts. Further evaluations of injury risk due to short falls should take into account the impact surface and head impact location, in addition to the fall height.